2010
DOI: 10.1037/a0020112
|View full text |Cite
|
Sign up to set email alerts
|

Temperamental emotionality in preschool-aged children and depressive disorders in parents: Associations in a large community sample.

Abstract: Researchers and clinicians have long hypothesized that there are temperamental vulnerabilities to depressive disorders. Despite the fact that individual differences in temperament should be evident in early childhood, most studies have focused on older youth and adults. We hypothesized that if early childhood temperament is a risk factor for depressive disorders, it should be associated with better-established risk markers, such parental depression. Hence, we examined the associations of laboratory-assessed po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(137 citation statements)
references
References 58 publications
(85 reference statements)
8
127
2
Order By: Relevance
“…Thus, parental anxiety disorders are associated with elevating risk of children to have anxiety disorders, SAD, and MDD. However, Olino et al (2010) found parental MDD and not anxiety disorders was related to parents' reports of 2-yearolds' internalizing behaviors. Methodological and age differences could account for these different findings, as Olino et al had very young children who were assessed via parent-reported symptoms and not diagnostic interviews.…”
Section: Parental Depression Anxiety and Sadmentioning
confidence: 79%
“…Thus, parental anxiety disorders are associated with elevating risk of children to have anxiety disorders, SAD, and MDD. However, Olino et al (2010) found parental MDD and not anxiety disorders was related to parents' reports of 2-yearolds' internalizing behaviors. Methodological and age differences could account for these different findings, as Olino et al had very young children who were assessed via parent-reported symptoms and not diagnostic interviews.…”
Section: Parental Depression Anxiety and Sadmentioning
confidence: 79%
“…Thus, they provide an important link to neuroscience on the biological bases of fearful temperament in other animals. Existing research utilizing batteries of laboratory tasks (e.g., Durbin, 2010;Durbin, Klein, Hayden, Buckley, & Moerk, 2005;Hayden, Klein, Durbin, & Olino, 2006;Olino, Klein, Dyson, Rose, & Durbin, 2010) has covered a range of manifestations of traits related to fear/fearlessness and inhibitory control. Tasks used for assessing fear proneness include contact-with-stranger tasks, performance tasks involving presentation of negative feedback or in which concerns about social scrutiny are heightened, exposure to typically fear-eliciting stimuli (e.g., scary objects, animals) or ambiguous/novel stimuli, or instructed engagement in acts that tend to elicit physical caution (such as walking across a balance beam).…”
Section: Behavioral Assessment Of Defensive Reactivity and Cognitive mentioning
confidence: 99%
“…Lab measures of fear proneness in preschoolers have been linked to familial risk for internalizing disorders (e.g., Olino et al, 2010), child anxiety disorders (e.g., Dougherty et al, 2011), and genetic polymorphisms . Moreover, laboratory research on dispositional fear (e.g., Dyson, Olino, Durbin, Goldsmith, & Klein, 2012) indicates that this construct is differentiable from individual differences in other negative emotions.…”
Section: Error-related Negativity (Ern)mentioning
confidence: 99%
See 1 more Smart Citation
“…The predictive validity of observational measures has been examined, with work establishing that such temperament indices show meaningful associations with children's psychophysiological systems (Fox, Henderson, Marshall, Nichols, & Ghera, 2005;Mackrell et al, 2014), moral development (Kochanska, Murray, Jacques, Koenig, & Vandegeest, 1996), and quality of parent-child relationships (Kochanska, Aksan, & Carlson, 2005). Observed affective traits (i.e., positive and negative emotionality) in preschoolers have been linked to maternal mood disorders (Durbin, Klein, Hayden, Buckley, & Moerk, 2005;Olino, Klein, Dyson, Rose, & Durbin, 2010), EEG asymmetries (Shankman, Tenke, Bruder, Durbin, Hayden, & Klein, 2005), serotonin transporter gene polymorphisms (Hayden, Dougherty, Maloney, Durbin, Olino, & Nurnberger et al, 2007), and the development of depressotypic cognitions and emerging internalizing symptoms in middle childhood (Dougherty, Klein, Durbin, Hayden, & Olino, 2010;Hayden, Klein, Durbin, & Olino, 2006;. Overall, observational assessments of temperament have demonstrated meaningful associations with both normal and abnormal processes, indicating their utility for developmental psychopathology research (Durbin, 2010).…”
Section: The Structure Of Observed Temperament In Preschoolersmentioning
confidence: 99%